2016
DOI: 10.1038/srep36359
|View full text |Cite
|
Sign up to set email alerts
|

A Comparative Metabolomics Approach Reveals Early Biomarkers for Metabolic Response to Acute Myocardial Infarction

Abstract: Discovery of novel biomarkers is critical for early diagnosis of acute coronary syndrome (ACS). Serum metabolite profiling of ST-elevation myocardial infarction (STEMI), unstable angina (UA) and healthy controls was performed using gas chromatography mass spectrometry (GC/MS), solid-phase microextraction coupled to gas chromatography mass spectrometry (SPME-GC/MS) and nuclear magnetic resonance (1H-NMR). Multivariate data analysis revealed a metabolic signature that could robustly discriminate STEMI patients f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
66
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 81 publications
(69 citation statements)
references
References 62 publications
3
66
0
Order By: Relevance
“…For instance, Ali et al. have described how HS‐SPME sampling with the use of DVB/CAR/PDMS coated fibers can be highly useful for extraction and further analysis by GC–MS of volatile metabolites, while avoiding derivatization step . Their data confirmed that an increase in acetone levels in the serum of some ST‐elevation myocardial infarction STEMI patients can be observed when compared to healthy controls.…”
Section: Spme In Biomedical and Clinical Studiesmentioning
confidence: 94%
See 1 more Smart Citation
“…For instance, Ali et al. have described how HS‐SPME sampling with the use of DVB/CAR/PDMS coated fibers can be highly useful for extraction and further analysis by GC–MS of volatile metabolites, while avoiding derivatization step . Their data confirmed that an increase in acetone levels in the serum of some ST‐elevation myocardial infarction STEMI patients can be observed when compared to healthy controls.…”
Section: Spme In Biomedical and Clinical Studiesmentioning
confidence: 94%
“…The ability to simultaneously determine changes in the hundreds of metabolites in a serum sample enables researchers to measure the multidirectional metabolic responses of living systems to pathophysiological stimuli. For instance, Ali et al have described how HS-SPME sampling with the use of DVB/CAR/PDMS coated fibers can be highly useful for extraction and further analysis by GC-MS of volatile metabolites, while avoiding derivatization step [55]. Their data confirmed that an increase in acetone levels in the serum of some ST-elevation myocardial infarction STEMI patients can be observed when compared to healthy controls.…”
Section: Head Space Spme In Untargeted Metabolomicsmentioning
confidence: 95%
“…For assessment of biological replicates, 100 μl of the methanolic extract was aliquoted in screw cap vials and left to evaporate under nitrogen gas stream until complete dryness. Derivatization was carried out as mentioned in Ali, Farag, Holvoet, Hanafi, and Gad ().…”
Section: Methodsmentioning
confidence: 99%
“…Recent report unveiled that NaHS-induced anti-atherosclerotic effects could also be partially through up-regulating ATP-Binding Cassette Transporter A1 (ABCA1) [116]. In addition to the therapeutic effects of H 2 S, H 2 S could be a biomarker for ST-elevation myocardial infarction and unstable angina [117]. …”
Section: Evidence Related To Atherosclerosis Prevention and Treatmentmentioning
confidence: 99%